Analysis of the Relationship Between Assimilate Production and Allocation and the Formation of Rice Quality - Jianming Tu; Fengting Wen; Feitong Li; Tingting Chen; Baohua Feng; Jie Xiong; Guanfu Fu; Yebo Qin; Wenting Wang (Agriculture)
Rice is one of China’s primary staple crops, serving as the main food source for over 60% of the population. With the resolution of basic food security issues in China in recent years, the demand for high-quality rice has been steadily increasing. The taste quality of rice, a crucial indicator for evaluating rice quality, has attracted more attention from consumers. Although factors like variety, growing environment, and cultivation methods affect rice taste quality, the underlying mechanisms remain unknown, and no reliable control methods exist. This study selected 10 major rice cultivars, including 6 indica and 4 japonica varieties, and compared their differences in taste quality, focusing on yield and its components, taste quality, and dry matter accumulation. Among the tested varieties, Songxiangjing 1018 had the best taste quality, but not the highest yield. Zhongzheyou 8, Huazheyou 261, and Quanyousimiao showed both excellent taste quality and high yield. There was no significant correlation between taste quality and yield, suggesting the feasibility of breeding rice varieties with both superior taste and high productivity. Correlation analysis indicated that dry matter mass and net photosynthetic rate were significantly positively correlated with yield, but not with taste quality, highlighting the complexity of taste quality formation. Using a membership function comprehensive evaluation method (combines the outputs of multiple membership functions into a single composite value using specific rules (e.g., weighted average, extremum, logical operations) to produce a new membership degree.), a rice variety selection system balancing yield and quality was constructed, and three varieties (Zhongzheyou 8, Huazheyou 261, and Quanyousimiao) were identified as having both high yield and excellent quality. The results of this study can provide a theoretical basis for research on cultivation techniques and variety breeding aimed at synergistically improving rice yield and quality.